RESPON AKTIVITAS TIKUS WISTAR JANTAN AKIBAT KONDISI DIET TINGGI SUKROSA DIUKUR MENGGUNAKAN PEREKAM AKTIVITAS: Activities Response Measurement on Male Wistar Rats With High Sucrose Diet Using Activity monitoring device - Wijaya, Yanuar Restu; Santoso, Koekoeh; Isdoni, Isdoni; Supiyani, Atin (LPPM Universitas Negeri Jakarta, 2016)
Excessive energi consumption play a role in increasing blood glucose levels (hyperglycemia), due to the inability of the hormone insulin to compensate the high blood glucose levels. Blood glucose receptor found in the hypothalamus of VMH (Ventro Medial Hypothalamus) and LH (the Lateral Hypothalamus) is able to detect and change the settings for the feeding activity. The aim of this study was to obtain the relationship between high sucrose feeding on male Wistar rats of behavior and activity. This method uses Wistar rats (Rattus norvegicus) as an animal model. Sixteen rats were grouped into 4 treatment groups. The first group was given additional feed 20% sucrose, the second group was given additional feed 40% sucrose, a third group was given additional feed 60% sucrose, and the last as a control group. This feed given continuously for 70 days.Observation of activities conducted using Opto-varimexÂ® auto-track system ver.4.31. The results showed an corellation between activity based doses of sucrose.